Obnova ali rehabilitacija koridorjev mestnih vodotokov - Bizjak, Aleš (Urbani izziv, 2001)
Analyses of the morphological state of urban streams and rivers in the Municipality of Ljubljana and research concerning the hydrographical network show that the condition of their morphological preservation is alarming. Efforts put in the new spatial development concept, guidelines and proposals for urban rehabilitation are therefore also an opportunity for rehabilitation measures on the municipal hydrographical network. Adequate care should be given to their improved morphological state even because of the recently adopted European framework water directive (annex 5), that after a certain period demands such a status of surface water in signatory countries.
Keywords: hidrologija; mesta; mestni predeli; obnova; razvojna strategija; sanacija; vodotoki